TINJAUAN YURIDIS TERHADAP KEDUDUKAN PENJAMIN PERORANGAN (BORGTOCHT) DALAM PENYELESAIAN KREDIT MACET DI PT. BANK PERKREDITAN RAKYAT DATA SEMARANG - Sabrina Zahara Noor Rahma; Siti Mahmudah (Universitas Djuanda, 2024)
The aim of this research is to analyze and examine individual guarantees guaranteed by debtors to creditors (Banks) in credit agreements. The approach method used in this research is normative juridical, with research specifications in descriptive analytical form. The results of the research show that individual guarantee arrangements are regulated in the Civil Code. An individual guarantee is a third party that guarantees all of the debtor's obligations to the creditor, if the debtor defaults. The position of individual guarantees at BPR DATA is an additional (accessory) that accompanies the main agreement. Credit with individual guarantees at BPR DATA is unsecured credit or KTA with a monthly salary payment system through the treasurer/finance department with guarantee/approval from the head of the company/institution. A debt guarantor in this case has the position that he is bound and responsible to the bank for all debts of the debtor. For every credit with individual guarantees, a guarantee agreement will be made privately, in the guarantee agreement the guarantor has special rights. As in BPR DATA, as the leader who guarantees the credit of its employees, in its implementation, if there is a default, the salary, social security, or insurance is deducted as credit repayment.